Impact of rehabilitation start time on functional outcomes after stroke - Satoshi Otokita; Hironori Uematsu; Susumu Kunisawa; Noriko Sasaki; Kiyohide Fushimi; Yuichi Imanaka (Medical Journals Sweden, 2021)
Objective: To investigate the optimum rehabilitation start timing for improved functional outcomes after stroke in Japan. Design: A retrospective database study. Subjects: A total of 140,655 patients with stroke from 1,161 acute hospitals in Japan. Only data for those patients who were discharged alive was included in the analysis. Methods: Activities of daily living were assessed. Comparisons were made using the rehabilitation start day after hospital admission. Reference day 2 was compared with days 1, 3, 4, 5, and 6 or later. Modified Rankin Scale at time of discharge was used as the primary outcome. In addition, cases of ischaemic stroke and haemorrhagic stroke were analysed as separate subgroups. Results: Univariate and multivariate logistic regression analyses showed that starting rehabilitation on day 2 resulted in a better outcome than starting on day 3 or later. There was no significant difference in outcome between starting rehabilitation on days 1 and 2 in all cases and subgroup of patient with infarction stroke. For a subgroup of patients with haemorrhagic stroke, starting rehabilitation on day 2 resulted in a better outcome than starting on day 1. Conclusion: Starting post-stroke rehabilitation on the day of admission or second day of hospitalization may be the optimum timing for functional outcomes. However, for haemorrhagic stroke, starting rehabilitation on the second day of hospitalization may be more effective than on the day of admission.